Brassinosteroids Attenuate Moderate High Temperature-Caused Decline in Tea Quality by Enhancing Theanine Biosynthesis in Camellia sinensis L. - Li, Xin; Wei, Ji-Peng; Ahammed, Golam J.; Zhang, Lan; Li, Yang; Yan, Peng; Zhang, Li-Ping; Han, Wen-Yan (Frontiers in Plant Science, 2018)
Temperature is a major environmental signal that governs plant growth and development. A moderately high ambient temperature alters plant metabolism without significant induction of heat–stress responses. Despite ancillary reports on the negative effect of warmer climate on tea quality, information on specific effect of sub high temperature (SHT) on theanine accumulation is scanty. L-Theanine is the most abundant free amino acid in tea (Camellia sinensis L.) leaves that contributes to the unique umami flavor of green tea infusion. Tea harvested in warmer months lacks distinctive umami taste due to low theanine content. In this study, we showed that SHT (35 °C) gradually decreased theanine concentration over time, which was closely associated with the SHT-induced suppression in theanine biosynthetic genes. 24-epibrassinolide (BR), a bioactive brassinosteroids, attenuated the SHT-induced reduction in theanine concentration by upregulating the transcript levels of theanine biosynthetic genes, such as ARGININE DECARBOXYLASE (CsADC), GLUTAMINE SYNTHETASE (CsGS), GLUTAMATE SYNTHASE (CsGOGAT) and THEANINE SYNTHASE (CsTS). Furthermore, time-course analysis of the activity of theanine biosynthetic enzyme reveals that BR-induced regulation of GS and GOGAT activity plays essential role in maintaining theanine content in tea leaves under SHT, which is consistent with the central position of GOGAT in theanine biosynthetic pathway. Therefore, it is convincing to propose that exogenous BR treatment can be advocated to improve summer tea quality by enhancing in vivo accumulation of theanine. However, a future challenge is to use this information on the role of BR in theanine biosynthesis and thermotolerance to further understand how BR may be tuned to benefit plant fitness for enhancing tea quality.